Physiotherapy under pressure: A cross-sectional study on the interplay between perfectionism, moral injury, and burnout - Daniel Biggs; Laura Blackburn; Cameron Black; Sivaramkumar Shanmugam (PLoS ONE, 2025)
Background Given the escalating challenges for UK-based physiotherapists in workload pressures, budget constraints, staff shortages and patient wait times, the profession (of 65,000 registered physiotherapists) necessitates immediate attention to the health and well-being of the therapists. This pioneering study aims to examine perfectionism, moral injury, and burnout among UK-based physiotherapists across the NHS, private practice, sports, and academia. Method This cross-sectional study utilised an online survey and implementation of Structure Equation Modelling (SEM) to assess the interplay of perfectionism (Multidimensional Perfectionism Scale-Short Form), moral injury (Moral Injury Symptoms Scale-Healthcare Professionals), and burnout (Shirom-Melamed Burnout Questionnaire). Our sample size calculation represents the UK physiotherapy profession, utilising a 95% confidence interval with a 5% margin of error. Findings Our analysis conducted on (n = 402) UK-based physiotherapists reveals significant burnout levels, with 96% of participants presenting with moderate to high burnout scores. SEM revealed perfectionism and moral injury collectively accounted for a substantial 62% of burnout variability, highlighting their sequential impact on burnout manifestation. Interpretation With such high levels of burnout, urgent intervention is paramount. Elevated burnout presents challenges for the physiotherapy profession as staff retention, accurate and effective patient care, and overall health are severely impacted due to burnout. Recognising and addressing perfectionism and moral injury, such as through amendment or development of policy, becomes pivotal to mitigate its impact on individual and collective health.